Two cases of spontaneous pneumomediastinum with pneumothorax in patients with COVID-19 associated pneumonia. (2020) - Oye, Monique; Ali, Aleem; Kandah, Fadi; Chowdhury, Nisha
Abstract: Coronavirus 2019 (COVID-19) is an infectious viral illness caused by severe acute respiratory syndrome virus coronavirus 2 (SARS-CoV-2). This disease mainly affects the lungs manifesting as acute lung injury, pneumonia, and acute respiratory distress syndrome. We describe two patients who developed concomitant spontaneous pneumothorax and pneumomediastinum in the setting of SARS-CoV-2 leading to acute hypoxic respiratory failure. This report adds to the increasing number of cases describing pulmonary complications of COVID-19 infection. Further studies are needed to ascertain the prognostic significance of these pulmonary complications in patients with SARS-CoV-2 infection. Highlights: A dangerous complication of COVID-19 is the development spontaneous pneumothorax and pneumomediastinum. CT chest is warranted in patients with declining respiratory status in the setting of COVID-19 infection. The risk of SPX and SPM may be increased with the addition of high flow nasal canula.